2016
DOI: 10.1590/1981-863720160003000033254
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with Oral Health-Related Quality of Life of preschool children in Southern Brazil

Abstract: Objective: The aim of this study was to assess the impact of socioeconomic factors and clinical conditions on the child oral health-related quality of life (COHRQoL) of preschool children. Methods: A cross-sectional study was conducted with a representative sample of 547 children of 0-5-years-old from Santa Maria, RS, Brazil, in 2013. Data were collect in the National Children's Vaccination Day Program by calibrated dentists. Clinical examinations assessed the prevalence of dental caries and dental trauma. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 16 publications
3
11
0
7
Order By: Relevance
“…Being older was an associated factor for the outcome in the health districts where children live, as demonstrated in other similar studies [2,3,12,20]. Corroborating other studies [21][22][23],…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Being older was an associated factor for the outcome in the health districts where children live, as demonstrated in other similar studies [2,3,12,20]. Corroborating other studies [21][22][23],…”
Section: Discussionsupporting
confidence: 81%
“…having had toothache in the last six months was a determining factor for d ≥1 among children investigated, compared to those who did not have this discomfort. These results may be indicative of the influence of unfavorable social and environmental factors in areas where the study population lives and whose accumulation of sociobiological risks for the occurrence and progression of caries may be continuously increasing with age [20][21][22][23][24]. In addition to revealing difficulties related to oral health surveillance actions planned for the study areas aimed at preventing and controlling early caries and monitoring groups at greater risk of having pain episodes of dental origin that require priority access to clinical treatment [25], as this condition has a negative impact on the quality of life of children and their families [21].…”
Section: Discussionmentioning
confidence: 99%
“…A lower level of schooling among parents/caregivers was associated with a greater impact on the OHRQoL of the preschoolers based on the parents/caregivers and children's self‐reports. Some studies have reported similar results, but they have only considered the reports of parents/caregivers using the ECOHIS . The habits of parents/caregivers and the family environment affect the health of children.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported similar results, but they have only considered the reports of parents/caregivers using the ECOHIS. 33,34 The habits of parents/caregivers and the family environment affect the health of children. A higher level of schooling is related to the search for greater care for one's children, which can minimize the consequences of oral problems due to greater access to dental services.…”
Section: Discussionmentioning
confidence: 99%
“…Dental caries is the most prevalent oral disease in children, with a large number of cases at both the national and regional levels [1][2] , presenting inequality in their distribution between Brazilian regions and population groups 3 , which significantly influences the quality of life of these individuals 4 . Individual characteristics, such as skin color and family income as well as the addition of fluoride in water also influenced the oral health profile of preschoolers in Brazil.…”
Section: Introductionmentioning
confidence: 99%